Religiosity of Polish Catholics in the UK: Attitude towards Faith, Affiliation, Membership and Religious Practices - Wódka, Marek (Religions, 2020)
This paper is based on sociological quantitative studies carried out in 2019 on a sample of 620 Polish Catholics living in London, Swindon, or Oxford. Those studies and their findings are limited only to those Catholics who make up the communities around major Polish institutions in the UK, such as Polish parishes, Saturday schools, and community houses. The goal of this paper is to describe selected aspects of Polish migrants’ religiosity in the new social and cultural milieu. What we focus on here is how Poles themselves describe their faith, how they understand and evaluate their membership of parishes or other religious communities, and how they approach religious practices, especially Sunday Mass attendance. We address the following questions: how do the Poles living abroad describe their attitudes towards faith? How many of them are active members of Polish parishes? What do their religious practices and membership of other community organisations look like? How do specific factors affect the results across these areas?